2021
DOI: 10.2147/itt.s280706
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Humoral Immune Responses in Covid-19 and Immunotherapeutic Approaches

Abstract: Coronavirus disease 2019 (Covid-19), caused by the novel coronavirus severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), can range in severity from asymptomatic to severe/critical disease. SARS-CoV-2 uses angiotensin-converting enzyme 2 to infect cells leading to a strong inflammatory response, which is most profound in patients who progress to severe Covid-19. Recent studies have begun to unravel some of the differences in the innate and adaptive immune response to SARS-CoV-2 in patients with differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 241 publications
(311 reference statements)
1
56
3
Order By: Relevance
“…Despite the promising viral neutralization profiles of vaccinated individuals with the Pfizer/BioNTech vaccines in our cohort, a recent sero-epidemiological study showed that reinfection among patients previously infected by SARS-CoV-2 occurs at a lower rate (0.23%) than infection occurrence within previously vaccinated patients (5.1%) [38]. These findings are inconsistent with the outcomes obtained by the seroneutralization tests, but viral neutralization tests consist of in vitro approaches that may not reflect the effect of cellular immunity within the human body [39,40], as this technique is based exclusively on antibody-antigen interactions. A study published in May 2020 reported that during a COVID-19 infection, the SARS-CoV-2 spike (S) protein was found to be a nondominant target of the human CD8+ T cell response and that the recognition of the SARS-CoV-2 M (Matrix) antigen was similarly strong to the S antigen, which is unlike other coronaviruses [41].…”
Section: Discussioncontrasting
confidence: 74%
“…Despite the promising viral neutralization profiles of vaccinated individuals with the Pfizer/BioNTech vaccines in our cohort, a recent sero-epidemiological study showed that reinfection among patients previously infected by SARS-CoV-2 occurs at a lower rate (0.23%) than infection occurrence within previously vaccinated patients (5.1%) [38]. These findings are inconsistent with the outcomes obtained by the seroneutralization tests, but viral neutralization tests consist of in vitro approaches that may not reflect the effect of cellular immunity within the human body [39,40], as this technique is based exclusively on antibody-antigen interactions. A study published in May 2020 reported that during a COVID-19 infection, the SARS-CoV-2 spike (S) protein was found to be a nondominant target of the human CD8+ T cell response and that the recognition of the SARS-CoV-2 M (Matrix) antigen was similarly strong to the S antigen, which is unlike other coronaviruses [41].…”
Section: Discussioncontrasting
confidence: 74%
“…Despite the promising viral neutralization pro les of vaccinated individuals with the P zer/BioNTech vaccines in our cohort, a recent sero-epidemiological study showed that reinfection among patients previously infected by SARS-CoV-2 occurs at a lower rate (0.23%) than infection occurrence within previously vaccinated patients (5.1%) [38]. These ndings are inconsistent with the outcomes obtained by the seroneutralization tests, but viral neutralization tests consist of in vitro approaches that may not re ect the effect of cellular immunity within the human body [39,40], as this technique is based exclusively on antibody-antigen interactions. A study published in May 2020 reported that during a COVID-19 infection, the SARS-CoV-2 spike (S) protein was found to be a nondominant target of the human CD8+ T cell response and that the recognition of the SARS-CoV-2 M (Matrix) antigen was similarly strong to the S antigen, which is unlike other coronaviruses [41].…”
Section: Discussioncontrasting
confidence: 74%
“…As of June 2021, with more than ∼3,840,223 deaths in total and 408,990 new cases each day, it is considered a serious threat to global public health. Although several vaccine candidates have initiated clinical testing, very little is currently known about their long-term humoral response ( Hasan et al, 2021 ). There are also currently no effective therapeutics ( Ho et al, 2004 ), calling for the urgent development of safe and effective therapeutics against COVID-19.…”
Section: Introductionmentioning
confidence: 99%